Mommy, mama, and me - Newman, Leslea; Thompson, Carol (Berkeley Tricycle Press, 2009)
A baby enjoys a number of fun activities with her two mothers.
Cover title.
On board pages.
Keywords: Lesbian mothers -- Juvenile fiction; Children of gay parents -- Juvenile fiction; Mother and child -- Juvenile fiction; Mothers -- Juvenile fiction; Board books; Picture books for children